Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Pada Materi Larutan Penyangga Menggunakan E-Modul Berbasis Scientific Critical Thinking (SCT) di SMA Negeri 4 Banjarmasin - Mahdian; Risma Ariyanti; Iriani Bakti (Postgraduate, University of Mataram, 2024)
This research is Classroom Action Research (PTK) which aims to determine the increase in critical thinking skills and student learning outcomes after learning using an e-module based on Scientific Critical Thinking (SCT) on buffer solution material. The research model developed by Kemmis and Mc Taggart consists of 4 stages, namely planning, implementing actions, observing and reflecting in each cycle. The research subjects were 36 students of class XI MIPA 4 SMA Negeri 4 Banjarmasin. Data collection on critical thinking abilities and student learning outcomes was carried out using test instruments. The research results showed that the students' critical thinking skills test in cycle I was 47.18 in the moderately critical category. while in cycle II it increased to a score of 81.08 in the very critical category. In the knowledge learning outcomes test, in cycle I it was 55.56 in the poor category and in cycle II it increased by 91.11 in the good category. Student responses also showed the agree category, thus the e-module based on Scientific Critical Thinking (SCT) on buffer solution material is suitable for use in learning to improve critical thinking skills and student learning outcomes.